2017
DOI: 10.18203/2320-1770.ijrcog20172919
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum IUCD: its acceptance and complications

Abstract: Background: Intra Uterine Contraceptive Device is the most commonly used reversible method of contraception worldwide. Immediate PPIUCD insertion is labelled when intra uterine device is inserted within 10 minutes to 48 hours of expulsion of placenta. The objective of the study was to determine the proportion of women accepting PPIUCD, factors influencing its acceptance, to look for side effects like bleeding disturbances, expulsion, lost strings, pain abdomen and pelvic infection etc. and the drop-out rates f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Health care workers explained the common reasons for removal: lower abdominal pain, irregular/excessive bleeding, feeling of needle prick sensation, resistance from family members, and vaginal discharge. Lower abdominal pain is a common complaint and ranges from 0.8 to 15% [12], [15], [16], [18]- [21], [27], [28]. The present study observed a higher rate.…”
Section: Complaints/complications/removalsupporting
confidence: 44%
“…Health care workers explained the common reasons for removal: lower abdominal pain, irregular/excessive bleeding, feeling of needle prick sensation, resistance from family members, and vaginal discharge. Lower abdominal pain is a common complaint and ranges from 0.8 to 15% [12], [15], [16], [18]- [21], [27], [28]. The present study observed a higher rate.…”
Section: Complaints/complications/removalsupporting
confidence: 44%
“…The incidence of loss to follow-up in our study (1.37%) was very much lower than that reported by the study conducted by Garg N et al (22.68%). 10 Study by Nayak et al and Verma A et al, reported much higher rates of loss of follow-up (58% and 40% respectively) Kittur et al, also reported similar higher rates of loss of follow-up. 15,16 The reason of low loss of follow-up rate in our study is because of the fact that it was done by a more accessible tertiary care hospital situated in a wellcommunicated location.…”
Section: Discussionmentioning
confidence: 79%
“…9 However, in another study by Garg N et al, showed that incidence of missing thread was more in case of Multiload 375 (25.77%) than Cu-T 380A (10-36%). 10 They also showed that bleeding (less than 11.3%) was less than incidence of missing thread in case of multiload 375. The possible explanation of this can be the initial length of string in both designs are different.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The incidence of missing threads varies between 5% and 25% in various studies. [4][5][6][7] Postpartum insertions are commonly associated with curling up of the thread in the enlarged uterine cavity. These patients should be evaluated with pelvic ultrasound and if need be on hysteroscopy.…”
Section: Case Reportmentioning
confidence: 99%